ANALYSIS OF APPROACHES TO THE EVALUATION OF QUALITY AND AVAILABILITY OF MUNICIPAL SERVICES - Bokareva, Elena; Panova, Alexandra; Barmenkova, Natalya; Boyko, Alexey; Sanginova, Lola (Revista Inclusiones, 2020)
The relevance of the work is determined by the need to develop conceptual approaches and methodological provisions for improving the organization of the provision of municipal services as one of the most important elements of the municipal economy, as well as by an increase in requirements for the quality and accessibility of these services both for the society as a whole and for individual customers. Currently, there is no comprehensive list of municipal services or system of quantitatively measurable characteristics of their quality, which complicates the overall objective assessment of the activities of local authorities in this direction. In municipalities, the results of the provision of municipal services are not systematically monitored and no analysis is made of the ratio of the costs of their provision with recoverable income and recipient satisfaction.